Mangrove (Rhizophoro Apiculata) Fannins As A Potential Corrosion Inhibitor For Aluminium In Acidic Medium. - Yahya, S.; Abdul Rahim, A.; Adnan, R. (2008)
Utilisation of a green corrosion inhibitor formulated from natural, biodegradable and nontoxic organic compounds in industries has been extensively explored by a*great number of researchers. Investigation of tannins extracted from Mangrove Rhizophoro Apiculata sp. as a corrosion inhibitor for aluminum alloy has been carried out in acidic medium.